2021
DOI: 10.3389/fpls.2021.650485
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Alleviates the KCl Salinity Stress of Malus hupehensis Rhed

Abstract: Applying large amounts of potash fertilizer in apple orchards for high apple quality and yield aggravates KCl stress. As a phytoalexin, resveratrol (Res) participates in plant resistance to biotic stress. However, its role in relation to KCl stress has never been reported. Herein we investigated the role of Res in KCl stress response of Malus hupehensis Rehd., a widely used apple rootstock in China which is sensitive to KCl stress. KCl-stressed apple seedlings showed significant wilting phenotype and decline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Nitrogen fertilization causes notable changes in N-cycling microbes, especially those in fungal communities (Guo et al, 2018 ; Du et al, 2019 ). Potassium is important in carbohydrate and protein metabolism and is recognized as an element that affects the quality (Li et al, 2021b ). The application of K fertilizer can increase crop yield and quality, and it is also widely used in preventing and treating plant and soil diseases (Pradip et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fertilization causes notable changes in N-cycling microbes, especially those in fungal communities (Guo et al, 2018 ; Du et al, 2019 ). Potassium is important in carbohydrate and protein metabolism and is recognized as an element that affects the quality (Li et al, 2021b ). The application of K fertilizer can increase crop yield and quality, and it is also widely used in preventing and treating plant and soil diseases (Pradip et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The perspective article is devoted to describing new approaches based on computational analysis to predict interactions between proteins related to different elements (Di Silvestre et al). Finally, within the 13 original research articles; eight of them are about the interactions between two or three elements, including non-essential ones, such as Fe-Cu, Si-Fe, Fe-P-S, S-N, Fe-Zn, K-Na, or P-Zn (Bernal and Kramer, 2021;Jian et al, 2021;Kakei et al, 2021;Li et al, 2021;Chaiwong et al;García et For instance, P deficiency, through organic acid release and rhizosphere acidification, can promote the mobilization of other nutrients, like Fe or Zn (Pueyo et al, 2021). In the same way, Si application can promote N and P acquisition by upregulating nitrate and phosphate transporters (Pavlovic et al, 2021).…”
Section: Editorial On the Research Topic Nutrient Interactions In Plantsmentioning
confidence: 99%
“…The perspective article is devoted to describing new approaches based on computational analysis to predict interactions between proteins related to different elements ( Di Silvestre et al ). Finally, within the 13 original research articles; eight of them are about the interactions between two or three elements, including non-essential ones, such as Fe-Cu, Si-Fe, Fe-P-S, S-N, Fe-Zn, K-Na, or P-Zn (Bernal and Kramer, 2021 ; Jian et al, 2021 ; Kakei et al, 2021 ; Li et al, 2021 ; Chaiwong et al ; García et al ; Suman et al ; Yu et al ); four of them are about the interactions among many nutrients, such as ionome-macronutrients, ionome-micronutrients, ionome-N ( Courbet et al ; D'Oria et al ; Zhang C. et al ; Zhang J. et al ); and one is devoted to the substitution of K by Na ( Mateus et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under KCl stress conditions, plants are typically stressed in three ways: ionic stress, osmotic stress, and oxidative damage ( Li et al, 2021a ; Li et al, 2021b ; Zheng et al, 2021 ). We found that SES1 can maintain the seedling K + /Na + balance, and the expression of K + transporter genes and ER stress-related genes were altered between WT and ses1 mutants under high potassium conditions during seedling establishment and post-germination growth.…”
Section: Discussionmentioning
confidence: 99%